Issues of Visual Search Methods in Digital Repositories - Gaona-García, Paulo Alonso; Montenegro-Marín, Carlos; Gaona-García, Elvis; Gómez-Acosta, Adriana; Hassan-Montero, Yusef; Hassan-Montero, Yusef (International Journal of Interactive Multimedia and Artificial Intelligence, 2019)
Repositories are important infrastructures which allow the dissemination of large collections of digital resources hosted in museums, libraries, academic institutions or specialized documentation centers. However, there are nowadays several limitations associated with irrelevant search results based on a knowledge area. Some studies have highlighted the major role of information visualization strategies based on Simple Knowledge Organization Systems (SKOS) so as to mitigate such difficulties. The main goal of this article is to present recommendations using information visualization based on SKOS for the development of navigational search interfaces in digital repositories focused on learning process. We use card sorting as methodology in order to obtain qualitative results in our study. As preliminary results we found that taxonomies in visual search engines improve the access to large collections of digital resources based on SKOS, but it depends on the design of taxonomy concepts defined in digital repositories. Finally, it is recommended that the creators of repositories focus their efforts on define levels of relationship and partnership between digital resources using knowledge representation structures like thesauri or ontologies; work with usable visualization interfaces like tree, radial or icicle; and link relevant metadata fields with the navigation structure.
Keywords: search interfaces; metadata; digital repositories; taxonomies; information visualization; Emerging; Scopus